Meningkatkan Hasil Belajar IPA Siswa Kelas III SD Negeri 009 Rambah Hilir Tentang Materi Lingkungan Tanun Pelajaran 2015/2016 - Murniati Murniati (STKIP Rokania Pasir Pangaraian, 2018)
Abstract, The subject of Natural Sciences (IPA) is one of the curricular courses in elementary school. Due to the low understanding of the students on the third grade of SD Negeri 009 Rambah Hilir, the authors make improvements in learning activities conducted in the State Elementary School 009 Rambah Hilir first semester of the 2015/2016 Lesson Year. Students less menggai learning materials and students less active in learning, seen from the results of science learning that still get a lot of low value. For that required improvement learning in accordance with learning that is by using cooperative learning model type Stad. This study aims to improve science learning outcomes through the Model Co-operative model of Stad Type for third grade students of SD Negeri 009 Rambah Hilir with a total of 20 students consisting of 12 male students and 8 female students. The type of research is classroom action research. The research procedure consists of planning, execution of action, observation and reflection. Instrument research in the form of learning devices and data collection tools (test sheets and student observation sheets). From the observation result shows that there is an increase of class average in cycle 1 that is 50% to 70% in cycle 2